Usuń niewymierność z mianownika :

a( 1/( √11) J) 1/(√3 ∙ √5)

b) 2/(√13) K) (-2)/(√7∙ √2)

c) (-3)/(√2) L) 1/(∛5)

d) (√3)/(√5) M) 2/(∛2)

e) (-√10)/(√3) N)(∛2)/(∛4)

f) 1/(2√3) O) (1+∛3)/(∛3)

g) (-1)/(3√2) P) (2+∛9)/(∛3)

h) (√2)/(-2√5)

i) (11+ √2)/(2√2)


/ - to znak ułamka

1

Odpowiedzi

Najlepsza Odpowiedź!
2009-11-09T20:12:33+01:00
A) 1/√11 = 1/√11 × √11/√11 = √11

b) 2/√13 = 2/√13 × √13/√13 = 2√13

c) -3/√2 = -3/√2 × √2/√2 = -3√2

d) √3/√5 = √3/√5 × √5/√5 = √15

e) -√10/√3 = -√10/√3 × √3/√3 = -√30

f) 1/2√3 = 1/√4×3 = 1/√12 × √12/√12 = 1√12

g) -1/3√2 = -1/√9×2 = -1/√18 × √18/√18 = -1√18

h) √2/-2√5 = √2/-√20 = √2/-√20 × √20/√20 = -√40

i) 11+ √2/2√2 = 11+√2/√8 × √8/√8 = 11+√32

j) 1/√3 ∙ √5 = 1/ √15 × √15/√15 = 1√15

k) -2/√7∙ √2 = -2/√14 × √14/√14 = -2 √14

l) 1/∛5 = 1/∛5 × ∛5/∛5 × ∛5 = (1∛5)²

m) 2/∛2 = 2/∛2 × ∛2/∛2 × ∛2 = (1∛2)²

n) ∛2/∛4 = ∛2/∛4 × ∛4/∛4 × ∛4 = ∛2 × ∛4 = ∛6

o) 1+∛3/∛3 = 1+∛3/∛3 × ∛3/∛3 ×∛3 = 1 +( ∛3)²

p) 2+∛9/∛3 = 2+∛9/∛3 × ∛3/∛3² = 2+ ∛12
1 5 1